EVALUASI PERFORMANSI PROTOKOL 6LOWPAN TERHADAP CSMA/CA PADA PERANGKAT IOT - Raphael Bianco Huwae; Andy Hidayat Jatmika; Noor Alamsyah (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2023)
The Internet of Things (IoT) has unique design requirements compared to typical network devices, particularly regarding energy efficiency and performance expectations. To meet the need for low power consumption and easy integration with existing IP network devices, 6LoWPAN is a viable option. 6LoWPAN is an adaptation layer that enables efficient transport of IPv6 packets within small link layer frames, such as those defined by IEEE 802.15.4. In this study, we conducted experiments to compare the delay and throughput performance of 6LoWPAN to the legacy CSMA/CA protocol, which uses IPv4 for addressing. In the experiment, NS3 was utilized to construct separate network system architectures for 6LoWPAN and CSMA/CA. The tests were conducted individually based on various research scenarios, with each scenario comprising 50 to 750 nodes and utilizing the same traffic type. The results were visualized for ease of comparison and analysis. Our experiment revealed that CSMA/CA outperforms 6LoWPAN in terms of both throughput and delay. Specifically, the average throughput of CSMA/CA was 2.345 times greater than that of 6LoWPAN, while the average delay was 2.54 times shorter.